Bi-functional performances of BaCe0.95Tb0.05O3−δ-based hollow fiber membranes for power generation and hydrogen permeation - Meng, X.; Shang, Y.; Meng, B.; Yang, N.; Tan, X.; Sunarso, J.; Liu, Shaomin (Elsevier Ltd, 2016)
Hydrogen separation and conversion to electricity are the two key processes in hydrogen economy. Here, a bi-functional BaCe0.95Tb0.05O3-δ (BCTb) coated NiO-BCTb hollow fiber is reported. Below 700 °C, BCTb has dominant proton conductivity while above 700 °C, the electronic conductivity becomes more significant, showing apparent behavior change from proton to mixed proton-electronic conductor. This enables its applicability as an electrolyte in solid oxide fuel cell (SOFC) below 700 °C and as a hydrogen permeation membrane beyond 700 °C. Microtubular SOFC showed a maximum power density of 552 mW cm−2 at 700 °C. Hydrogen permeation membrane demonstrated the highest flux of 0.53 mL min−1 cm−2 at 850 °C. The transition from proton to mixed protonic-electronic conductor was substantiated by the abrupt reduction in the open circuit voltage of the SOFC operated above 700 °C and in the protonic transport number from 0.94 to 0.81 with the temperature rise from 700 to 850 °C.